Diffusion tensor-based analysis of white matter in dogs with idiopathic epilepsy - Beckmann, Katrin M.; Wang-Leandro, Adriano; Steffen, Frank; Richter, Henning; Dennler, Matthias; Bektas, Rima; Carrera, Ines; Haller, Sven (Frontiers in Veterinary Science, 2023)
The understanding of epileptic seizures pathogenesis has evolved over time, and it is now generally accepted that not only cortical and subcortical areas are involved, but also the connection of these regions in the white matter (WM). Recent human neuroimaging studies confirmed involvement of the WM in several epilepsy syndromes. Neuroimaging studies investigating the WM integrity with diffusion tensor imaging (DTI) in canine idiopathic epilepsy are lacking. The present study aimed to test the hypothesis that WM diffusion changes can be found in dogs affected by idiopathic epilepsy.Twenty-six dogs with idiopathic epilepsy (15 Border Collies, 11 Greater Swiss Mountain dogs) and 24 healthy controls (11 Beagle dogs, 5 Border Collies, 8 Greater Swiss Mountain dogs) were prospectively enrolled. Most dogs with idiopathic epilepsy (17/26) were enrolled within 3 months after seizure onset. Diffusion tensor imaging of the brain with 32 diffusion directions (low b value = 0 s/mm 2 ; maximal b value = 800 s/mm 2 ) was performed in a 3 Tesla scanner. Tract Based Spatial Statistics (TBSS), a voxel-based approach, was used to investigate changes in fractional anisotropy (FA) and mean diffusivity (MD) in idiopathic epilepsy group compared to healthy control group.Additionally, FA and MD were investigated in the region of corpus callosum and cingulate white matter in both groups.We observed subtle changes in WM DTI between idiopathic epilepsy group and healthy control group limited to cingulate WM, with a significant lower FA in the idiopathic epilepsy group compared to the healthy control group in the region of interest (ROI) approach (p = 0.027). No significant changes were found between idiopathic epilepsy group and healthy control group in the TBSS analysis and in corpus callosum in the ROI approach.This study supports the cingulate area as a target structure in canine epilepsy. The subtle changes only might be explained by the short duration of epilepsy, small sample sizes and the higher variability in canine brain anatomy. Furthermore, all included dogs showed generalized tonic colonic seizures, possibly affected by a generalized epilepsy syndrome, which are also associated with less pronounced DTI changes in humans than focal epilepsy syndromes.